Understanding the dynamics driving obesity in socioeconomically deprived urban neighbourhoods: an expert-based systems map - Fleur ter Ellen; Joost Oude Groeniger; Karien Stronks; Luc L. Hagenaars; Carlijn B.M. Kamphuis; Joreintje D. Mackenbach; Mariëlle A. Beenackers; Karen Freijer; Pieter Coenen; Maartje Poelman; Karen M. Oude Hengel; Frank J. van Lenthe (BMC Medicine)
Abstract Background Over the past decades, the prevalence of obesity among adults has rapidly increased, particularly in socioeconomically deprived urban neighbourhoods. To better understand the complex mechanisms behind this trend, we created a system map exposing the underlying system driving obesity prevalence in socioeconomically deprived urban neighbourhoods over the last three decades in the Netherlands. Methods We conducted Group Model Building (GMB) sessions with a group of thirteen interdisciplinary experts to develop a Causal Loop Diagram (CLD) of the obesogenic system. Using system-based analysis, the underlying system dynamics were interpreted. Results The CLD demonstrates the food environment, physical activity environment, socioeconomic environment and socio-political environment, and their interactions. We identified the following overarching reinforcing dynamics in the obesogenic system in socioeconomically deprived urban neighbourhoods: (1) adverse socioeconomic conditions and an unhealthy food environment reinforced each other, (2) increased social distance between social groups and adverse socioeconomic conditions reinforced each other and (3) increased social distance between institutions and communities and the normalisation of unhealthy behaviours reinforced each other. These deeper system dynamics further reinforced chronic stress, sedentary behaviour, sleeping problems, unhealthy diets and reduced physical activity over time. In turn, these dynamics led to the emergent result of rising obesity prevalence in socioeconomically deprived urban neighbourhoods over the past decades. Conclusions Our study sheds light on the system dynamics leading to neighbourhoods with an unhealthy food environment, challenging socioeconomic conditions, a widening distance between social groups and an infrastructure that discouraged physical activity while promoting sedentary behaviour. Our insights can form the basis for the development of an integrated approach aimed at reshaping the obesogenic system in socioeconomically deprived urban neighbourhoods.